Student Understanding of PAI Subjects in Improving the Results of Madrasa Science Competitions at MTs Al-Mu'min Tasikmalaya - Siti Nur Janah; Asep Ahmad Sya’ban; Entin Kurniatin; Aa Fachry Fathul Barri; Dede Aji Mardani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study aims to determine the effect of PAI subject abilities on students participating in Madrasah Science Competition in 2023 at MTs.al-Mu'min and to find out how students can help students in working on madrasa scientific competency questions integrated with PAI subjects. This research is a qualitative descriptive research with research subjects namely Social Sciences, Natural Sciences, Mathematics and PAI teachers as well as students of the Madrasah Science Competition in 2023. The research population is 8 people, consisting of 3 KSM 2023 participants, 1 MAPEL IPA teacher, 1 teacher Mapel Social Sciences, 1 Mathematics Mapel Teacher and 2 Mapel Teachers of Islamic Religious Education. Data collection techniques in this study use semi-structured interview techniques. The results showed that the ability of students' understanding in PAI subjects and PAI teacher assistance was very influential on the results of integrated madrasah science competencies.